The Electronic Government Policy-Based Green Constitution Towards Good Governance - Nilam Firmandayu; Khalid Eltayeb Elfaki (Lembaga Contrarius Indonesia, 2023)
In fact, e-government policy in Indonesia has not yet finished discussing regulations and implementations in government institutions. E-government policies are still regulated at the institutional field specifically or still at the respective regional governments. The nature of the policy is still partial so that there is no structural regulation as a rigid policy implementer that regulates the implementation of e-government in Indonesia. However, the implementation of e-government that uses technology, information and communication equipment will have a negative impact on environmental sustainability, one of them is an increase e-waste from the government sector. This research uses normative legal analysis to find legal facts and formulate a green constitution-based electronic government policy model to realize efficiency, effectiveness, accountability, and transparency of governance and public services towards good governance. This research proves the urgency of implementing regulations as an innovation model for e-government policies based on a green constitution to ensure the reduction of e-waste in Indonesia using green ICT. Therefore, it is important to develop guiding regulations which are Government Regulation for the implementation of e-government in both the central and regional government bureaucracies.